Nature's Pharmacy: Herbal Interventions in Rheumatoid Arthritis Treatment: A Comprehensive Review - Mittal, Vishnu; Sharma, Anjali; Barak, Aashima; Singhal, Abhinav (Current Rheumatology Reviews, 2025)
Rheumatoid Arthritis (RA) is an inflammatory disease that causes severe joint destruction and persistent inflammation. This review aims to evaluate the efficacy, safety, and mechanisms of action of various herbal interventions in managing RA, providing valuable insights for patients and healthcare practitioners. To investigate the anti-inflammatory and antioxidant properties of selected herbal interventions, including turmeric, ginger, Boswellia serrata (frankincense), green tea, and Ashwagandha, to assess their potential as complementary treatments for RA, a comprehensive analysis is performed on the anti-inflammatory mechanisms and antioxidant effects of selected herbs. Emphasis is placed on the modulation of key inflammatory pathways and their ability to counteract oxidative stress, which are crucial factors in RA progression. Safety profiles and potential adverse effects of herbal remedies are also scrutinized. The review reveals promising evidence supporting the efficacy of turmeric and ginger in alleviating RA symptoms by modulating inflammatory pathways. Additionally, Boswellia serrata shows potential as an adjunct therapy for joint health and inflammation. The antioxidant-rich properties of green tea and Ashwagandha are highlighted, suggesting their role in counteracting oxidative stress associated with RA. In conclusion, while herbal remedies like turmeric, ginger, Boswellia serrata, green tea, and Ashwagandha offer potential complementary treatments for RA, their safety profiles and adverse effects warrant careful consideration. Rigorous clinical trials are needed to confirm their efficacy and safety, highlighting the necessity for further research in this area. These findings are crucial for patients and healthcare providers in making informed decisions about incorporating herbal interventions into RA treatment strategies.
Keywords: Rheumatoid arthritis